Nitrogen, phosphorus and potassium content of six biofertilizers used for fertigation in organic production system - Almeida, Luciana Gomes de; Candian, Joara; Cardoso, Antonio Ismael Inacio; Grassi Filho, Helio (Comunicata Scientiae, 2021)
The goal of this research was to study the contents of N, P and K of six biofertilizers during the fermentation process. The experiment consisted of six biofertilizers and five dates of evaluation during the fermentation period (3, 7, 15, 22 and 30 days after preparation (DAP) of biofertilizers). The biofertilizers were prepared on the same basis for fermentation, differing from each other by adding an ingredient in 15 L of water: T1 = castor bean cake (2 kg), T2 = blood meal (2 kg), T3 = hull and horn powder (2 kg), T4 = bone meal (2 kg), T5 = blood meal (1 kg); T6 = bone meal (1 kg). The experimental design was a randomized block design with three replicates. The following variables were analyzed: contents of N, P and K and the electrical conductivity. The biofertilizer hoof and horn powder showed, at all times, higher N content than the others, reaching a maximum content of 6.77 g L-1, whereas the bone meal (1 and 2 kg) had the lowest level, reaching a maximum of 1.43 and 1.93 g L-1, respectively, all at 30 DAP. At all dates of evaluation, the castor bean cake and hoof and horn powder biofertilizers showed higher P content, with an average of 3.23 and 2.61 g L-1, respectively, than bone meal (1 and 2 kg) biofertilizers. Castor bean cake biofertilizer presented at all dates of evaluation higher content of K, average of 2.49 g L-1, than hoof and horn powder, blood meal (1 and 2 kg), bone meal (1 or 2 kg) biofertilizers, averaging 1.86; 1.69; 1.60; 1.57 to 1.68 g L-1, respectively, which did not differ each other. Regardless of the type of biofertilizer, the K content did not change, the N content and the electrical conductivity increased, and the P content reduced during the time of fermentation until 30 DAP